2020
DOI: 10.1111/jnc.15105
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting promotes adult hippocampal neuronal differentiation by activating GSK‐3β in 3xTg‐AD mice

Abstract: Moderate dietary restriction or reduced calorie intake is known to reduce blood sugar, increase insulin sensitivity (Johnson et al., 2016), alleviate aging, reduce age-related chronic diseases, and prolong life expectancy (Barger, Walford, & Weindruch, 2003). Many studies have been conducted into the beneficial effects of dietary restriction on the cardiovascular, immune, and endocrine systems (Brandhorst &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 96 publications
(128 reference statements)
0
22
0
5
Order By: Relevance
“…Upon close examination of the available literature on IF in rodents, we wonder whether publication bias might be playing a role in skewing it towards reporting positive results. We noticed high diversity in its effects on adult neurogenesis, with an overwhelming majority of reports showing variable positive impact (Apple et al, 2019;Baik et al, 2020;Brandhorst et al, 2015;Cao et al, 2022;Dias et al, 2021;Kaptan et al, 2015;Kim et al, 2015;Kitamura et al, 2006;Kumar et al, 2009;Lee et al, 2000;Lee et al, 2002b;Lee et al, 2002a;Li et al, 2020;Park et al, 2013;Wu et al, 2008) and very few showing no effect or a mild impairment (Bondolfi et al, 2004;Staples et al, 2017). In some reviews, even studies reporting no effect are cited as evidence for improved neurogenesis upon IF.…”
Section: Discussionmentioning
confidence: 99%
“…Upon close examination of the available literature on IF in rodents, we wonder whether publication bias might be playing a role in skewing it towards reporting positive results. We noticed high diversity in its effects on adult neurogenesis, with an overwhelming majority of reports showing variable positive impact (Apple et al, 2019;Baik et al, 2020;Brandhorst et al, 2015;Cao et al, 2022;Dias et al, 2021;Kaptan et al, 2015;Kim et al, 2015;Kitamura et al, 2006;Kumar et al, 2009;Lee et al, 2000;Lee et al, 2002b;Lee et al, 2002a;Li et al, 2020;Park et al, 2013;Wu et al, 2008) and very few showing no effect or a mild impairment (Bondolfi et al, 2004;Staples et al, 2017). In some reviews, even studies reporting no effect are cited as evidence for improved neurogenesis upon IF.…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction is a particularly important confounding factor to consider when comparing TAM chow-fed to vehicle chow-fed animals. Although Bondolfi and colleagues found no effect of caloric restriction on hippocampal neurogenesis in male mice aged 3–11 months ( Bondolfi et al, 2004 ), others have found that dietary restriction and intermittent fasting enhance neuronal differentiation in the adult hippocampus ( Hornsby et al, 2016 ; Li et al, 2020 ). Both the caloric restriction during TAM feeding and the return to normal feeding after the end of TAM chow may therefore be affecting neurogenesis in TAM-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction is a particularly important confounding factor to consider when comparing TAM chow-fed to vehicle chow-fed animals. Though Bondolfi et al found no effect of caloric restriction on hippocampal neurogenesis in male mice aged 3-11 months (Bondolfi et al, 2004), others have found that dietary restriction and intermittent fasting enhance neuronal differentiation in the adult hippocampus (Hornsby et al, 2016; Li et al, 2020). Both the caloric restriction during TAM feeding and the return to normal feeding after the end of TAM chow may therefore be affecting neurogenesis in TAM-fed mice.…”
Section: Discussionmentioning
confidence: 99%